HUBUNGAN BERAT BADAN LAHIR RENDAH DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RUANG PERINATOLOGI RSUD BIAK NUMFOR PROVINSI PAPUA - Ijawati S. Dimara, Rahelina; Purwati, Anik; Safitri, Rani (NHM PRESS, 2024)
Low birth weight are the babies with birth weight < 2500 grams. Low birth weight babies have many problems in the body due to the body organs that have not developed perfectly, so that in these low birth weight babies can lead to asphyxia neonatorum. Asphyxia neonatorum is a state of respiratory failure that occurs spontaneously and regularly soon after birth. This study aims to determine the relationship between low birth weight and the incidence of asphyxia neonatorum in the perinatology room at Biak Numfor Hospital, Papua Province. This research uses observational analytics with a cross-sectional design. The population of this study were all babies born LBW in January-March 2024 at Biak Numfor District Hospital, treated in the Perinatology room with a sample of 59 babies with a sampling technique using purposive sampling. Data collection on low birth weight uses weight scales and APGAR scores to determine asphyxia neonatorum. Data were analyzed using the chi square test. The results showed that 67.8% of babies were LBW, 25.4% were LBW babies, and 6.8% were LBW babies. LBW babies with moderate asphyxia are the largest number at 37.3%. The chi square test results show that there is a relationship between low birth weight and the incidence of asphyxia neonatorum in the perinatology room at Biak Numfor Regional Hospital, Papua Province with a p-value of 0.029 < 0.05